Prolonged infusion piperacillin-tazobactam decreases mortality and improves outcomes in severely ill patients: results of a systematic review and meta-analysis - Rhodes, Nathaniel J.; Liu, Jiajun; O'Donnell, J. Nicholas; Dulhunty, Joel M.; Abdul Aziz, Mohd. Hafiz; Berko, Patsy Y.; Nadler, Barbara; Lipman, Jeffrey; Roberts, Jason A. (The Society of Critical Care Medicine and Wolters Kluwer Health, Inc., 2018)
Objective: